Attitudes towards sight-singing among choir students in the Faculty of Music, UiTM Shah Alam / Olivva Kusmas - Kusmas, Olivva (Faculty of Music, 2014)
The purpose of this study was to investigate the attitudes towards sight-singing among choir students in the Faculty of Music, UiTM Shah Alam. Specifically, this study looked at three elements: perceptions towards sight-singing, problems faced in sight-singing, and how students overcome problems in sight-singing. The sample comprised of 69 students enrolled in the choir class from three programs in the Faculty of Music, UiTM, Shah Alam: Music Education (MU220), Composition (MU221), and Performance (MU222). Independent variables such as program and gender were used to compare descriptive statistics between sections and each item in each section. Data were analyzed through descriptive statistics employing One-way ANOVA to compare between programs and independent-sample t-test to compare between genders. The overall finding showed that choir students from all three programs were similar in their attitudes and perceptions towards sight singing in choir class. There were no significant differences between the three programs for all three aspects being investigated. No significant differences were found between the males and females for all three sections (p > .05). Pearson's correlation was used to access the relationship between problems in sight-singing (section C) that was divided into two parts: sight-singing problems and choir sight-singing problems, and overcoming problems in sight-singing (section D). Interestingly, both parts in section C showed a strong positive correlation to each other (r > .5) meaning that the choir students who experienced problems in sight-singing faced problems in choir sight-singing…